Fish alimentation of the Carangidae Family of the estuarine logoon complex in cananéia, São Paulo, Brazil - Höfling, José Claudio; Ferreira, Luiza Ishikawa; Ribeiro Neto, Francisco Borba; Paiva Filho, Alfredo Martins; Soares, Cintia Paiva; Silva, Mauricio Solera R. da (Bioikos – Título não-corrente, 1998)
Estuaries are areas of great ecological importance owing to their biological productivity, which makes them important providers of fish and crustacean species of high economic value. They are also important for small-scale fishermen. The objective of this study is to determine the eating habits of fish, which are found in Cananéia, São Paulo, Brazil, through stomach content analysis. The trophic spectrum analysis of the Carangidae family species studied allows the basic alimentation of crustacean and fish eaters: Selene setapins, S. vomer, Caranx latus, Oligoplites saliens and O. saurus; crustacean and polychaete eaters for Chloroscombrus chrysurus and Trachinotus goodei; mollusks, crustaceans and fishes eaters forTrachinotus carolinusand mollusks and fishes for Trachinotus falcatus.